Agroecology as a political concept: A case study of the Southeast geopolitical region of Nigeria - Ume, Chukwuma Otum; Justus Liebig University Giessen (My University, 2023)
This study is based on a case study of an agroecology group from rural agricultural communities in Southeast Nigeria. In 2016, researchers from the Centre for Agroecology, Coventry University, started an agroecology extension service that led to the establishment of an agroecology group in Southeast Nigeria. The agroecology farmers utilized sustainable methods such as multiple cropping, zero tillage, and intercropping. In addition, they established a trade-by-barter market system for food exchanges and a peer-to-peer indigenous knowledge exchange network. Women make up 89% of the agroecology farmers in the group. Apart from the agroecology farmers, there are also the "conventional" farmers in the study area. The so-called conventional farmers also belong to the FADAMA project, which seeks to increase agricultural productivity by supplying external chemical inputs and seeds to the farmers. Using this case study and employing the feminist economics theory, this PhD study answered the question of how agroecology might be linked to food security among smallholder farmers. Specifically, the objectives of the research were to (i) uncover how the literature on food security and nutrition in Africa framed the role of agroecology, (ii) investigate the pathways through which agroecology improves food security and nutrition of smallholder farmers, and (iii) provide a better understanding on how agroecology promotes agency in pursuing reproduction activities among rural farmers? The study begins with a narrative review whereby I engage with empirical literature on agroecology and food security to find the pathways through which agroecology leads to food and nutrition security. The literature review is followed by an empirical investigation. I used a mixed-method approach combining quantitative and context-specific qualitative data to test the pathways emanating from the literature review empirically. The primary data for this study was collected from 334 small-scale farmers (comprising 111 agroecology farmers and 223 non-agroecology farmers) and 24 interviews with women farmers in the agroecology group. A quantile propensity score matching was employed to analyze the quantitative data, while the qualitative interviews were analyzed using thematic analysis. The study found that in both the agroecology and the conventional groups, farmers had little access to land, even lower ownership of land, little exposure to extension services, and no access to financial credits. Consequently, the study sample predominantly consisted of marginalized smallholder farmers. In contrast to the expectation of conventional hypotheses, this study demonstrates that, on average, agroecology farmers experienced lower levels of food insecurity and exhibited higher dietary diversity scores. Exploring more detail within the agroecology group via a quantile semi-parametric propensity score matching, the study further revealed that women excluded from conventional extension services derived greater benefits from their participation in the agroecology group. Similarly, the research indicated that the most substantial improvements in food security and nutrition were observed among farmers who balanced their food sources between self-provisioning and market-based approaches instead of exclusively relying on one of these sources. Notably, this strategy was predominantly adopted by women. For these farmers, the agroecology group serves as an alternative avenue for accessing crucial resources and knowledge that would otherwise be out of reach within the capitalist food system. This access empowers them to achieve their nutritional goals. Findings from this study suggest that implementing different agroecological practices influences and determines the broader social relations that define prevailing food systems and vice versa. The success of sustainable and innovative agroecological practices often hinges on the social capital and knowledge networks that farmers build within their communities. These social relationships facilitate the dissemination of information, the sharing of resources, and the collective adoption of agroecological techniques. Conversely, the strengthened social bonds and shared experiences that result from social relationships can directly influence the adoption and success of agroecological sustainable practices on the farm. In essence, the study emphasizes that the holistic approach of agroecology extends beyond the field and encompasses the social fabric of farming communities. This integrated approach ultimately contributes to improved production efficiency and enhanced food security among smallholder farmers.
Keywords: Agroecology; Food Security; Nutrition; Nigeria; Gender; ddc:300